Experiences of a nature-based intervention program in a northern natural setting: A longitudinal case study of two women with stress-related illness. Issue 1 (31st December 2023) - Johansson, Gunilla; Engström, Åsa; Juuso, Päivi
ABSTRACT: Purpose: This study explored the experiences of people with stress-related illness participating in a nature-based intervention programme in a northern natural setting. Methods: A longitudinal case study was conducted with two women participating in a nature-based intervention programme on a farm. Data were collected by semi-structured interviews, diaries, rating scales, and self-assessment. Qualitative data were analysed by qualitative content analysis and quantitative data are presented descriptively. Results: The theme of finding a source for recovery and well-being permeates all categories. The participants perceived the farm and nature to be a calming refuge; they learned to be in the present and could manage the tasks. In togetherness with each other and the facilitator on the farm they felt understood and confident, experienced joy, and found opportunities for change. They gained knowledge and positive memories and found new approaches in life. Self-assessment questionnaires indicated improvements of functioning in everyday life and reduced stress-related exhaustion at the end of the NBI programme. Conclusions: Nature-based interventions lasting for a relatively short period seem to promote health and may be a complement to other treatments of stress-related illness. Further research is needed with a larger number of participants and in various natural settings.